Hubungan Stres Dengan Kualitas Tidur Pada Mahasiswa Tingkat Akhir - Tri Okta Ratnaningtyas; Dwi Fitriani (Edu Masda Journal, 2019)
Students are one of the early adult groups who have a lot of activities, so that students become a group at risk of having poor sleep quality. One of the causes of poor sleep quality is due to stress factor. This research was conducted to identify the relationship of stress with sleep quality in the final level students at STIKes Kharisma Persada.  This research used analytic observational research with quantitative approach and cross sectional design. Population in this research were all final level students of STIKes Kharisma Persada, totaling 203 people. Sample in this research was 133 respondents were taken by sampling technique that is simple random sampling. Data collection using questionnaires and data analysis using chi square statistical tests. Based on the results of this research showed the majority of respondents aged are 21 years and female sex. Based on the results of univariate analysis of stress variables, it is known that most respondents who experience stress have difficulty relaxing at a mild level and most respondents experience stress with excessive reactions at moderate levels. Meanwhile, the results of univariate analysis of sleep quality variables are known that most respondents have good sleep quality based on aspects of subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disorders, and use of sleeping drugs and most of the respondents have moderate sleep quality based on the aspect of activity interruption. Based on bivariate analysis with chi square test, it is known that there is a relationship between stress and sleep quality with p value = 0.016. There is a relationship between stress and sleep quality in final level students.